Management of Drug-Resistant Tuberculosis in Pregnancy: Epidemiology, Challenges, and Treatment Strategies - Gautam, Jagjot; Paul, Amrit; Saha, Subhasish; Mal, Satyam; Mohanta, Tanmay; Pradhan, Sabitri; Saharia, Niharjyoti; Sao, Anil Parasnath (Journal of Neonatal Surgery, 2025)
Pregnancy-related drug-resistant TB poses several difficulties because of the complicated treatment plans, teratogenicity hazards, and the paucity of safety evidence on second-line TB medications. Research trials frequently leave pregnant women out, resulting in a lack of evidence-based recommendations for treating DR-TB. Increased morbidity, premature birth, and low birth weight are just a few of the major health problems the illness poses to both the mother and the newborn. Newer medications like delamanid and bedaquiline have shown encouraging safety profiles during pregnancy, and recent studies have concentrated on improving treatment approaches. To bridge the knowledge gap, recent clinical trials that include pregnant individuals include Smart4TB and Beat-TB. The World Health Organization (WHO) has started to address this problem by updating recommendations to encourage the use of more recent, all-oral regimens. To improve the outcomes for mothers and newborns, a multidisciplinary strategy comprising obstetricians, pulmonologists, and infectious disease specialists is essential. To improve treatment adherence, psychosocial and nutritional assistance are also crucial. Future studies should further include pregnant women in clinical trials to ensure safer and more efficient methods of treating DR-TB during pregnancy.